Ecologia integral como referencial educativo-pastoral a partir da Laudato Si' - Selbach, Luiz Carlos (2022)
The concept of integral ecology in Pope Francis’ Encyclical Laudato Si’ proposes a new understanding of the environmental perspective and human behavior in all its relationships. Above all, it points out ways of a new hope for a future shared by all humanity. Consolidating a regenerated society, with full life for all creation, presupposes overcoming social, economic, cultural and spiritual challenges that present themselves in the context of contemporaneity through an educational path. The growing crises that humanity is going through demand that we start to look at them not in an isolated way, but in an integrated way. The Encyclical Laudato Si’ is an invitation to the urgency of a conversion, much deeper than a simple request for forgiveness: it is ecological conversion that underlies the call for care and regeneration of the common home as an element of salvation for the future of humanity and of the planet. Pope Francis enhances the concept of integral ecology by pointing to an ecological educational and spiritual itinerary as a reference for understanding and re-signification of educational-pastoral practices and processes. The present research, immersed in the thought and actions of Pope Francis, which corroborate the concept of integral ecology and the epistemological assumptions imbricated therein, intends to point to a new way of thinking and undertaking educational-pastoral processes in light of this. The method of bibliographic research chosen to undertake this journey makes it possible to discover the need for a broad and qualified understanding of the concept of integral ecology and the urgency of its capillarization in all possible spheres and contexts: ecclesiastical, educational, social, political and economic. Evangelizing and educating on the basis of integral ecology is the new salvation that the world needs. Therefore, it is urgent that the educational-pastoral processes assume this reference.